Culicoides midge bites modulate the host response and impact on bluetongue virus infection in sheep. - Nonito Pages; Emmanuel Bréard; Céline Urien; Sandra Talavera; Cyril Viarouge; Cristina Lorca-Oro; Luc Jouneau; Bernard Charley; Stéphan Zientara; Albert Bensaid; David Solanes; Joan Pujols; et al. (PLoS ONE)
Many haematophagous insects produce factors that help their blood meal and coincidently favor pathogen transmission. However nothing is known about the ability of Culicoides midges to interfere with the infectivity of the viruses they transmit. Among these, Bluetongue Virus (BTV) induces a hemorrhagic fever- type disease and its recent emergence in Europe had a major economical impact. We observed that needle inoculation of BTV8 in the site of uninfected C. nubeculosus feeding reduced viraemia and clinical disease intensity compared to plain needle inoculation. The sheep that developed the highest local inflammatory reaction had the lowest viral load, suggesting that the inflammatory response to midge bites may participate in the individual sensitivity to BTV viraemia development. Conversely compared to needle inoculation, inoculation of BTV8 by infected C. nubeculosus bites promoted viraemia and clinical symptom expression, in association with delayed IFN- induced gene expression and retarded neutralizing antibody responses. The effects of uninfected and infected midge bites on BTV viraemia and on the host response indicate that BTV transmission by infected midges is the most reliable experimental method to study the physio-pathological events relevant to a natural infection and to pertinent vaccine evaluation in the target species. It also leads the way to identify the promoting viral infectivity factors of infected Culicoides in order to possibly develop new control strategies against BTV and other Culicoides transmitted viruses.